China Plus One Policy: A Strategic Approach amid De-escalation of Trade Tensions - Galani, Despina Danai; Kanellopoulos, Anastasios Nikolaos (HAPSc Policy Briefs Series, 2025)
With trade uncertainty between China and US escalating after Trump’s re-election, supply chain resilience and the relocation of manufacturing and production lines away from China to other developing countries, or even back to the US, is more current than ever emerging as a strategic choice. The strategy of China Plus One aiming to offer competitive advantage to companies diversifying their activities outside of China, is brought to surface and faces reversal; becoming competitive disadvantage. The recent 90-day truce between US and China, that will allow Chinese goods to be traded at tariffs much lower of the initial 145% threat, combined with the US Federal Court’s ruling that tariffs are illegal, shifts the landscape. Companies that diversified early into alternative markets like Vietnam or Mexico, once seen as strategically agile, may now find themselves at a cost disadvantage compared to firms that retained full operations in China, as lower o or no tariffs re-favor centralized production.